Collaborative source–grid–load frequency regulation strategy for DC sending-end power grid considering electrolytic aluminum participation - Xing, Chao; Xi, Xinze; He, Xin; Deng, Can; Zhang, Mingqiang (Frontiers in Energy Research, 2024)
As renewable energy sources are increasingly being integrated into power systems, traditional frequency regulation methods have faced challenges, such as reduced system inertia and diminished regulatory capacity. We present a source–grid–load collaborative control strategy for the participation of electrolytic aluminum in the frequency regulation of the DC sending-end power grid. First, the frequency response characteristics of the ultrahigh-voltage DC (UHVDC) sending-end system are analyzed, and an electrolytic aluminum load model is established. Then, a hierarchical source–grid–load control strategy is proposed. The upper-layer control assigns the frequency support tasks to synchronous generators, electrolytic aluminum stations, and UHVDC systems based on the frequency dead zones. The lower-layer control aims to minimize the cost of controlling the electrolytic aluminum loads by distributing power adjustment commands to each electrolytic aluminum series within the power station. Simulations were conducted, and the results validate the effectiveness and economic benefits of the proposed strategy in reducing the control costs while maintaining system stability.